2021
DOI: 10.2188/jea.je20190217
|View full text |Cite
|
Sign up to set email alerts
|

Association of Eating Alone With Depression Among Older Adults Living Alone: Role of Poor Social Networks

Abstract: Objectives: Eating alone is associated with an increased risk of depression symptoms. This association may be confounded by poor social networks. The present study aimed to determine the role of poor social networks in the association of eating alone with depression symptoms, focusing on cohabitation status. Methods: Seven hundred and ten community-dwelling older adults were categorized according to their eating style and social network size, evaluated using an abbreviated version of the Lubben Social Network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
0
10
1
Order By: Relevance
“…However, the independent association between eating status and disability identified in this study is not consistent with that in previous studies, which have shown that older men living with others and eating alone have an increased risk of mortality ( 12 ), and eating alone has been associated with nutritional risk ( 5 ), poor appetite ( 9 ), and depression ( 6 , 10 , 11 ). In this study, the relationship between eating alone and functional disability was nullified by adjusting for physical function, lifestyle, and depression, thus suggesting that these variables may mediate the association between eating alone and disability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the independent association between eating status and disability identified in this study is not consistent with that in previous studies, which have shown that older men living with others and eating alone have an increased risk of mortality ( 12 ), and eating alone has been associated with nutritional risk ( 5 ), poor appetite ( 9 ), and depression ( 6 , 10 , 11 ). In this study, the relationship between eating alone and functional disability was nullified by adjusting for physical function, lifestyle, and depression, thus suggesting that these variables may mediate the association between eating alone and disability.…”
Section: Discussioncontrasting
confidence: 99%
“…Eating alone has been identified as one of the risk factors for malnutrition associated with eating behavior ( 5 ), reducing dietary variety ( 6 , 7 ), nutrition intake ( 8 ), and appetite ( 9 ). Several studies have indicated that eating alone is associated with depression ( 6 , 10 , 11 ) and mortality among older men living with others ( 12 ). Reduced social networks and social support after losing a spouse or peers and friends among older adults can lead them to eat alone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that people who eat with same-sex friends experience increased energy intake [19], and those who frequently eat together are more likely to feel better about themselves and have a wider social network that provides them with social and emotional support [20]. In addition, Sakurai et al [21] reported that despite living with others, those who eat alone are more prone to depression. Thus, eating with others in a community-based salon for the elderly may offer an opportunity for older adults to eat together outside the household, expand their social network, and further prevent malnutrition and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a multiple regression analysis was conducted to identify the impact of general and solo dining-related characteristics, SDS, and NSDS on depression. For the regression model, we developed a causality based on some earlier studies [ 13 , 14 ]. We used the Kolmogorov–Smirnov test to verify the normality of the data, and the Breusch–Pagan test to verify the homoscedasticity of residuals for linear regression.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on college students, eating alone had a significant positive correlation with depression [ 12 ]. However, most studies that investigated the relationships between eating alone and the occurrence of mental health problems, particularly depression, focused on the elderly [ 13 , 14 ]. In particular, it is difficult to find a study that analyzes the association among solo dining, motivation for solitude, and depression in university students.…”
Section: Introductionmentioning
confidence: 99%